The impact of teaching experimental research on-line: Research-informed teaching and COVID-19. Issue 2 (May 2021) - Higgins, R.; Murphy, F.; Hogg, P.
Abstract: Introduction: As part of the BSc (Hons) Diagnostic Radiography programme students learn and undertake research relevant to their development as first post radiographers (dose optimisation and image quality) within the Research-Informed Teaching experience (RiTe). Due to the COVID-19 pandemic, the delivery of RiTe to our year 2 students was moved to an online format using Microsoft Teams and Blackboard Collaborate and focused on a key area of current practice - COVID-19 and chest X-ray imaging. Within RiTe students are placed into collaborative enquiry-based learning (CEBL) groups to share tasks, but to also support and learn from one another. Methods: An online survey was used to explore the year 2 student cohort task value and self-efficacy of this online version of RiTe. Results: A 73% (32/44) response rate was achieved. Students found the online version of RiTe to be a positive learning and development experience. There was strong agreement that they not only found it relevant to their area of practice (task-value), but also strongly agreed that they understood and could master the skills taught (self-efficacy). Conclusion: This online version of RiTe was effectively structured to help scaffold student learning and development of research data analysis skills despite the lack of face-to-face teaching. The students also valued the topic area (COVID-19 and chest X-ray imaging). A blended learning approach with RiTe will be used next year with a combination of collaborative online teaching and physical data collection and analysis in the university-based X-ray imaging laboratory. Further evaluation and data collection will also be undertaken. Implications for practice: University-based empirical work in groups to learn about research can be replaced by an online mechanism whilst still maintaining task-value and acceptable self-efficacy.